Descrição cariótica e novas ocorrências de cromossomos supranuméricos em Moenkhausia Eigenmann, 1903 (Characiformes: Characidae) - Nascimento, Cristiano Neves do [UNESP] (2015)
The cytogenetic mapping of repetitive DNA has been applied in several studies in fish, which allowed a better characterization about the biodiversity and genomic evolution of Neotropical ichthyofauna. Among the several fish species living in this area, the genus Moenkhausia, one of the specious groups inside Characidae, is remarkable. From a cytogenetic point of view, this genus show variations in diploid numbers of 48 to 50 chromosomes, as well as the occurrence of B chromosomes in different species/populations. However, cytogenetic studies in Moenkhausia collected at different rivers from the Amazon and Upper Paraguay River basins are scarce, as well as studies investigating the chromosomal distribution of repetitive DNAs in different species. In this sense, the present study aimed to characterize the karyotypes of Moenkhausia cosmops, M. cf. forestii, M. cf. nigromarginata, M. oligolepis and Moenkhausia sp. collected at different sites in the Amazon and Upper Paraguay River basins. All species were analyzed using classical (conventional staining with Giemsa, localization of NORs by impregnation with Silver nitrate and C-banding) and molecular (fluorescent in situ hybridization with 5S and 18S rDNA, H1 histone, U2 snDNA and telomeric sequences (TTAGGG)n probes). All the herein analyzed species showed 2n=50 chromosomes, with different karyotype formulas. C-banding evidenced similar patterns of heterochromatin distribution in all species, except in M. cf. nigromarginata. Silver nitrate staining evidenced simple Ag-NORs in all species and FISH with 18S rDNA probes confirmed these results e revealed additional sites in M. oligolepis. The 5S rDNA was interstitially located in multiple sites in all species. Notably, both ribosomal sites were found in synteny in one population of M. oligolepis. The H1 histone sites were co-located in a single pair with 18S rDNA and the U2 snDNA was located at multiple sites in all species. Additionally, the ...